The importance of vector control for the control and elimination of vector-borne diseases. - Anne L Wilson; Orin Courtenay; Louise A Kelly-Hope; Thomas W Scott; Willem Takken; Steve J Torr; Steve W Lindsay (Public Library of Science (PLoS), 2020)
Vector-borne diseases (VBDs) such as malaria, dengue, and leishmaniasis exert a huge burden of morbidity and mortality worldwide, particularly affecting the poorest of the poor. The principal method by which these diseases are controlled is through vector control, which has a long and distinguished history. Vector control, to a greater extent than drugs or vaccines, has been responsible for shrinking the map of many VBDs. Here, we describe the history of vector control programmes worldwide from the late 1800s to date. Pre 1940, vector control relied on a thorough understanding of vector ecology and epidemiology, and implementation of environmental management tailored to the ecology and behaviour of local vector species. This complex understanding was replaced by a simplified dependency on a handful of insecticide-based tools, particularly for malaria control, without an adequate understanding of entomology and epidemiology and without proper monitoring and evaluation. With the rising threat from insecticide-resistant vectors, global environmental change, and the need to incorporate more vector control interventions to eliminate these diseases, we advocate for continued investment in evidence-based vector control. There is a need to return to vector control approaches based on a thorough knowledge of the determinants of pathogen transmission, which utilise a range of insecticide and non-insecticide-based approaches in a locally tailored manner for more effective and sustainable vector control.